THE REPRESENTATION OF THE WOMAN ARTIST AS DEPICTED IN THE LITERATURE AND FILM WORKS OF SLAVENKA DRAKULIC AND JULIE TAYMOR (Philological Studies, 2022)
Cultural practices including the media, literature, film, advertising, and art that can be categorized under its wide spectrum, are a mirror that reflects the state of society. Though this thesis could also be turned vice versa, arguing that the cultural pattern and the values in society are created, strengthened or undermined through the forms of representation in popular culture, art, and literature. It is extremely important to question the representation of the modern woman in popular culture, or more specifically, what are the gender perspectives that are founded and destroyed through the film and literary depictions of the woman artist. This paper will explore the processes of coding and decoding gender stereotypes through the portrayal of one of the most famous female artists of the twentieth century, the Mexican painter Frida Kahlo. For that purpose, we will make a comparative analysis of two works about Kahlo - the film "Frida" (2002) directed by Julie Taymor, starring Selma Hayek and Alfred Molina, and the novel Frida's Bed (2008) by the Croatian author Slavenka Drakulic, translated from Croatian to Macedonian by Aleksandar Prokopiev. Through the reflections on the body as a source of female experience, on the one hand, and female creativity in the shadow of the patriarchal culture, on the other hand, we will actually try to re-examine the normative gender roles in society and sexist artistic perspective that inevitably lead to discrimination and gender inequality